The Phenomenon of Mobility, a Development Challenge for the City Of Algiers - OUAFA LOUAFI (Journal of Contemporary Urban Affairs, 2019)
Urban displacements are a major challenge for the economic and social development of the city and are a sign of the quality of life. They are defined by less congestion, less pollution, congestion and urban sprawl. In Algeria, the new urban policies are seen as the beginning of a positive transformation of the city's situation, which degradation seems to have originated in a lack of coordination between planning, the deregulation of the transport sector and the urban planning of cities. Therefore, it is necessary to develop a transportation policy based on a logic of sustainable development of the urban area where the optimization of mobility is required. The purpose of this article is to demonstrate the importance of developing the most adequate operating policies for the various modes of transport that are the most appropriate in the capital city of Algiers and to implement an investment program in the management of mobility in order to transform the city.